Feeding and Nutrition of Anteaters - Valdes, Eduardo V. (2011)
The superorder Xenarthra (former Edentata) is grouped into two orders, Cingulata (armadillos) and Pilosa (anteaters and sloths). These are special mammals that show unique traits: (1) the existence of secondary articulations called xenarthrales located between the lumbar vertebrae and the spinal column; (2) the presence of fused pelvic bones; and (3) very low metabolic rate and variable body temperatures, which allow xenarthrans to conserve energy. They are also highly specialized, but diverse in terms of dietary needs. Xenarthrans include strict folivores such as the three-toed sloth (Bradypodidae), omnivore-generalists such as the two-toed sloth (Choloepus spp.), specialized carnivores such as the giant anteater (Mymecophaga tridactyla), and the tamanduas (Tamandua tetradactyla, T. mexicana). Armadillos vary in their diet, with certain species feeding mainly on ants and termites but others, such as the common Dasypus novemcinctus, are omnivorous.